Implementing Environmental Accounts Case Studies from Eastern and Southern Africa - Hassan, Rashid M.; Hassan, Rashid M.; Mungatana, Eric D.; Mungatana, Eric D. (Eco-Efficiency in Industry and Science,, 2013)
This report on natural resource and environmental accounting in one of the world’s least developed zones is predicated on a wealth approach to sustainable development that recognizes the need for information on all of a nation’s assets, including, for example, potable water, as well as how these might change or evolve over time. Under these criteria, a nation that manages its natural wealth intelligently may actually increase its net natural assets. Namibia’s wildlife reserves have an ongoing and evolving value far in excess of their commodity value as a source of meat, or even of ivory. Thus, this volume assesses how effectively polities in southern and eastern Africa have implemented the more complex set of metrics that make up the UN’s Integrated System of Environmental and Economic Accounts (SEEA), which replaced the former System of National Accounts—a measure of production alone. Leaving aside human and social capital for a future volume, the book should be viewed as a crucial first step in developing indicators for total wealth in the countries covered by the case studies, which include Kenya, Uganda, Tanzania, Ethiopia, Mozambique and South Africa. These case studies experiment with implementing the SEAA in sub-Saharan nations known to suffer from the ‘resource curse’: their wealth in resources and commodities has allowed inflows of liquidity, yet this cash has not funded crucial developments in infrastructure or education. What’s more, resource-driven economies are highly vulnerable to commodity price mutability. The new measures of wealth deployed here offer more hope for the future in these countries than they themselves would once have allowed for.